2017
DOI: 10.18632/oncotarget.20779
|View full text |Cite
|
Sign up to set email alerts
|

Metformin treatment after the hypoxia-ischemia attenuates brain injury in newborn rats

Abstract: Neonatal hypoxic-ischemic (HI) brain injury is a devastating disease that often leads to death and detrimental neurological deficits. The present study was designed to evaluate the ability of metformin to provide neuroprotection in a model of neonatal hypoxic-ischemic brain injury and to study the associated molecular mechanisms behind these protective effects. Here, we found that metformin treatment remarkably attenuated brain infarct volumes and brain edema at 24 h after HI injury, and the neuroprotection of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 60 publications
2
31
1
Order By: Relevance
“…Additionally, high dose exendin-4 administration resulted in significantly higher levels of brain cAMP, suggesting involvement of the cAMP signalling pathway, also proposed in other studies ( Teramoto et al , 2011 ; Kim et al , 2017 ). Interestingly, metformin, another type 2 diabetes mellitus medication with diverse pharmacological activities, also ameliorates brain infarction in neonatal hypoxic-ischaemic rats ( Fang et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, high dose exendin-4 administration resulted in significantly higher levels of brain cAMP, suggesting involvement of the cAMP signalling pathway, also proposed in other studies ( Teramoto et al , 2011 ; Kim et al , 2017 ). Interestingly, metformin, another type 2 diabetes mellitus medication with diverse pharmacological activities, also ameliorates brain infarction in neonatal hypoxic-ischaemic rats ( Fang et al , 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, age impacts on brain functioning, once it was observed in a previous study that the same neonatal anoxia model, at PND 90, decreased the %OAT and the percentage of time spent on the closed arm was significantly higher in adult male subjected to neonatal anoxia than in control animals Which altered cellular mechanisms would be responsible for these damages? Accumulated evidence has acknowledged the following events: neuronal apoptosis, reactive gliosis, oxidative stress, excitotoxicity, inflammation and disruption of blood-brain barrier as linked to the neonatal brain damage induced by neonatal anoxia (Beilharz et al, 1995;Buwalda et al, 1995;Wei et al, 2004;Borutaite et al, 2013;Fang et al, 2017;Li et al, 2017;Li et al, 2018). Notably, sex-specificity in many of these processes occurs in normal brain development and may be a reason to male and female differentially respond to neonatal oxygen deprivation, which in turn alters their developmental program and cognitive functions, as also shown in the onset of ontogenetic reflexes and somatic development (Kumar et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have shown that metformin treatment has improved locomotor recovery after SCI [31,32], but the underlying mechanism of its action is still unclear, especially its role in reducing oxidative stress or promoting axonal regeneration after SCI. Moreover, the other studies have indicated that metformin can protect against hypoxic-ischemic brain injury-induced neuronal cell apoptosis [33]. However, it is unknown whether metformin protects against neuronal damage after SCI by promoting axonal regeneration.…”
Section: Introductionmentioning
confidence: 99%